Some of the theoretical basis of local self-government in the Czech Republic - Petr Pospíšil; Marian Lebiedzik (DANUBE: Law, Economics and Social Issues Review, 2017)
In the valid legislation of the Czech Republic, we do not find a clear and completely unambiguous definition of the concept of "self-government". Nonetheless, it is an institute traditionally used and with content defined in a particular way by the theory of administrative law or administrative science in the context of the division of public administration into state administration and self-government. Self-government usually refers to public administration (i.e. administration of public affairs) carried out by public law bodies other than the state. These public law bodies are most often public corporations, which perform specific tasks within territorial self-government, professional self-government and interest group self-government. The aim of the paper is to provide an interpretation of the theoretical and legislative definition of the concept of self-government and specifically to focus on territorial self-government. In processing the paper and fulfilling the set goal, the authors will primarily use scientific methods of analysis, synthesis, description, explanation and comparison. Based on the presentation and analysis of theoretical opinions on the issue, the applicable legislation of territorial self-government and insights from public law-related practice, the authors conclude that it is appropriate to consider a more detailed (yet open) definition of self-governing tasks of municipalities and regions in the future.
Keywords: 330; Czech Republic; Public Administration; Self-government; Territorial Self-government; Territorial Self-governing Units; Municipalities; Regions